2003
DOI: 10.1093/ajcn/77.3.622
|View full text |Cite
|
Sign up to set email alerts
|

Whole-grain and fiber intake and the incidence of type 2 diabetes

Abstract: An inverse association between whole-grain intake and the risk of type 2 diabetes was found. The similar result for cereal fiber intake suggests that the whole-grain association is due to cereal fiber or another factor related to cereal fiber intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
339
2
17

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 534 publications
(386 citation statements)
references
References 25 publications
21
339
2
17
Order By: Relevance
“…Despite some evidence therefore to suggest that an increased intake of soluble fibre improves glycaemic control, soluble fibre intake is not associated with incident T2DM in prospective studies Montonen et al, 2003). A possible explanation is that the quantity of fibre consumed in an average diet does not contain sufficient soluble fibre, particularly of the gel-forming type, to have a distinguishable effect on glycaemic control.…”
Section: Fibrementioning
confidence: 96%
See 3 more Smart Citations
“…Despite some evidence therefore to suggest that an increased intake of soluble fibre improves glycaemic control, soluble fibre intake is not associated with incident T2DM in prospective studies Montonen et al, 2003). A possible explanation is that the quantity of fibre consumed in an average diet does not contain sufficient soluble fibre, particularly of the gel-forming type, to have a distinguishable effect on glycaemic control.…”
Section: Fibrementioning
confidence: 96%
“…After adjustment for potential confounding factors, people consuming around 3 servings per day of whole grain products had a risk reduction in the order of 20-30% compared with low consumers of whole grain products with a dose-response across quintiles of whole grain food intake (Liu et al, 2000;Meyer et al, 2000;Fung et al, 2002). A smaller study carried out in Finland did not find a statistically significant difference in incident T2DM when comparing consumers of whole grain foods above and below the extreme quartiles of intake, although there was a trend suggesting a reduced risk of developing T2DM among larger consumers of whole grain foods (Montonen et al, 2003). Adding dietary glycaemic load into the models did not change the association between whole grain food intake and incident T2DM (Liu et al, 2000;Meyer et al, 2000).…”
Section: Prospective Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of fruit and vegetables (Snowdon & Phillips, 1985;Colditz et al, 1992;Feskens et al, 1995;Ford & Mokdad, 2001) and whole grains (Liu et al, 2000;Meyer et al, 2000;Fung et al, 2002;Montonen et al, 2003) have shown inverse associations with the risk of diabetes. The associations are independent of obesity, a major risk factor for diabetes.…”
Section: Introductionmentioning
confidence: 99%